Відновлення розвитку креативної економіки в регіонах України - Поснова, Тетяна Вікторівна; Теліщук, Мирослава Миколаївна (ДУ «Інститут регіональних досліджень ім. М. І. Долішнього НАН України», 2023)
Розвиток креативної економіки завжди характеризувався виразними регіональними диспропорціями, які ще більше посилились в умовах воєнного стану. Розглянуто сучасний стан креативної економіки в регіонах. Наголошується на необхідності внесення змін до Закону України «Про засади державної регіональної політики», Державної стратегії регіонального розвитку на 2021-2027 роки відповідно до Плану відновленняУкраїни, розробленого Кабінетом МіністрівУкраїни. За результатами післявоєнної відбудови та трансформації Україна може набути широкі можливості завдяки високому рівню ІТрозвитку в багатьох сферах економіки та динамічному зростанню креативних індустрій, які мають високий мультиплікатор доданої вартості. Відновлення креативної економіки в регіонах дасть змогу підтримати їхню економіку,зупинити відтік фахівців з країни,запровадити нові культурні та соціальні ініціативи відповідно до історичного й культурного контексту в різних регіонах, у такий спосіб зменшивши їхню диспропорційність.

The regional vector of creative economy development is aimed at the formation of infrastructural support, distribution of creative goods and services, and evolution of ways to attract funds. For successful competition in the internal and foreign markets, it is no longer enough for regions to have only material resources, but they must also have a strong creative potential in order to respond promptly to the challenges of the external environment. At the same time, the development of the creative economy has always been characterized by distinct regional disparities, which have become further intensified under martial law. In this regard, it is necessary to create a new regional development policy, which requires a comprehensive analysis of the current situation related to the war and its impact on the situation in Ukraine as a whole and in the regions and territorial communities. Since the industrial cities and regions of Ukraine have suffered and are suffering the greatest destruction, this significantly affects now and will affect in the future the placement of productive forces on the territory of Ukraine and will determine the possibility of people returning or not returning to these industrial cities and regions. The article considers the current state of the creative economy in the regions and the need to amend the Law of Ukraine “On Principles of Regional Policy” and the 2021-2027 State Strategy for Regional Development in accordance with Ukraine’s Recovery Plan by the Cabinet of Ministers of Ukraine. The post-war development of regional creative economy centers should take place on the basis of updated legislation on regional development. In addition, the State Fund for Reconstruction and Regional Development should be created since the reconstruction of regions affected territories requires significant financial resources, which are not available in local budgets and are quite small in the state budget of Ukraine. The restoration of the creative economy in the regions will make it possible to support their economy, stop the outflow of specialists from the country, and introduce new cultural and social initiativesin accordance with the historical and cultural context in different regions, thus reducing their imbalances.
Keywords: креативна економіка; креативна індустрія; регіональний розвиток; післявоєнне відновлення; creative economy; creative industry; regional development; post-war recovery